"Some call it resilience": A profile of dynamic resilience-related factors in older adult survivors of childhood institutional adversity and maltreatment. (September 2020) - Mc Gee, Shauna L.; Maercker, Andreas; Carr, Alan; Thoma, Myriam V.
Abstract: Background: Childhood adversity and maltreatment can have lasting negative effects into later life. However, emerging research suggests that certain factors may facilitate resilience in adults with experiences of childhood adversity and maltreatment. Objective: Using conceptual models of resilience, this qualitative study investigated factors associated with resilience in older adult survivors of childhood institutional adversity and maltreatment. Participants and setting: Participants consisted of 17 adults, 10 females and 7 males, aged between 50–77 years (mean age = 60 years). All participants had experienced childhood adversity and maltreatment within institutional care settings during childhood and/or adolescence. Methods: In-depth, semi-structured interviews were conducted, lasting between 60−120 min. Transcribed interviews were analysed using the Framework Analysis method. Results: Nine themes were derived from the data, including core, internal, and external resilience factors: Individual characteristics, personality characteristics, support systems, goal attainment, adaptive belief systems, processing, influential events and experiences, recognition and collective identity, and access to services. Conclusions: Results support a dynamic concept of resilience that can be understood not only as an inherent trait, but also as a learnable set of behaviours, thoughts, and attitudes, which can be supported by external resources in an older adults' environment. These findings add a novel contribution to the literature in the identification of a distinct cluster of personal and contextual factors underpinning resilience in this sample of survivors of childhood institutional adversity and maltreatment, which may inform the psychological treatment of this population and provide a focus for further research.